Hubungan Tingkat Pengetahuan dan Tingkat Kepatuhan Minum Obat Pasien Diabetes Melitus Tipe 2 di Puskesmas Pakis - Mayang Aditya Ayuning Siwi; Marshanda Rachelia Firdausi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Diabetes mellitus is a disease characterized by hyperglycemia and metabolic disorders of carbohydrates, fats, and proteins associated with absolute or relative deficiency of insulin action or secretion, this requires long-term treatment, where the role of health workers and patients is very important, especially in terms of patient medication compliance which is the spearhead for successful therapy. Compliance is influenced by several factors, especially education. This study was conducted to determine the relationship between the level of knowledge and the level of compliance with taking medication for type 2 diabetes mellitus patients at Pakis Health Center. This research design is a descriptive quantitative study with a cross sectional approach to 100 patients with purposive sampling method using the DKQ-24 and MMAS-8 questionnaires. Of the total patients, the most patients were 46-59 years old (49%), female gender (81%), high school (81%), not working (42%), 1-10 years of suffering (85%), the number of drugs received> 2 (54%), there were comorbidities (59%), sufficient knowledge (65%), and moderate compliance (74%). Spearman's rho correlation analysis showed a p-value of 0.0001 and a correlation coefficient (r) of 0.610. These results indicate that there is a strong relationship between the level of knowledge and the level of compliance with taking medication for type 2 diabetes mellitus patients at Pakis Health Center.